Rational Design of Two-Dimensional Bimetallic Wave Structures from Zigzag Chains via Site-Specific Coordination around the 2,6-Naphthalenediphosphonic Acid Motif - Bulut, Aysun; Zorlu, Yunus; Worle, Michael; Pasa, Salih; Kurt, Huseyin; Zubieta, Jon; Beckmann, Jens; Yucesan, Gundog (WILEY-V C H VERLAG GMBH, 2016)
We report the synthesis of a novel aromatic 2,6-naphthalenediphosphonic acid (2,6-NDPA-H-4) and the rational design of molecular, one-, two-, and three-dimensional structures of the resulting copper organophosphonate materials: [{Cu(terpy)}(2,6-NDPA-H-3)][{Cu(terpy)}(2,6-NDPA-H-3)(2,6-NDPA-H-2)]center dot 3H(2)O (2), [{Cu(terpy)}VO2(2,6-NDPA-H)]center dot H2O (4), [{Cu-(terpy)} VO2(2,6-NDPA-H)] (3) and [{Cu(H2O)}(NDPA)(0.5)] (1). Engineering the copper coordination sphere and pH-controlled phosphonate protonation enabled the site specific dimensional evolution of CuII-organophosphonate frameworks exploiting the 2deprotonated phosphonate oxygen arms.
Keywords: Metal-organic frameworks; Metal-organic solids; Organophosphonates; Ligand design; Coordination modes; Copper; Magnetic properties; CRYSTAL-STRUCTURES; TEMPERATURE-DEPENDENCE; HYDROTHERMAL SYNTHESIS; 1ST ROUTE; CHEMISTRY; PHOSPHONATE; LIGANDS; SYSTEM; LAYERS